UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI DAUR AIR MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Reni Setiowati (Universitas Muhammadiyah Purwokerto, 2018)
The research was supported by the low learning outcome on science subject for fifth B grade SD Negeri 1 Bojongsari student. This is evidenced from the low cognitive evaluation based on the evaluation of data subjects of natural science that shows that there are still many students who have not attained mastery learning. The research was aimed at improving students’ natural science learning outcome on the material of the water cycle through Problem Based learning fifth-grade student of the elementary school. The subjects were the students of fifth grade SD Negeri 1 Bojongsari, there were 24 students, 10 male and 14 female ones. This classroom action research was conducted in two cycles. The data were collected from test and observation. An evaluation test was used to collect the data of the cognitive aspect of written tests conducted at the end of each cycle. Affective and psychomotoric evaluation worksheet was used to collect the data of affective and phsycomotoric aspect. The result showed the achievement mean in cycle I was 68,3 and then increased to 81,67 in cycle II. The result of the affective aspect the percentage in cycle I was 70,42% and increased to 85,62%. The result of phsycomotoric aspect the percentage in cycle I was 80,03% and increased to 90,1%. Finally, it can be drawn a conclusion that Problem Based Learning can improve students’ natural science learning outcome.